2020
DOI: 10.3171/2020.1.focus19899
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformation presenting with epilepsy: a multimodal approach to diagnosis and treatment

Abstract: Arteriovenous malformation (AVM) presenting with epilepsy significantly impacts patient quality of life, and it should be considered very much a seizure disorder. Although hemorrhage prevention is the primary treatment aim of AVM surgery, seizure control should also be at the forefront of therapeutic management. Several hemodynamic and morphological characteristics of AVM have been identified to be associated with seizure presentation. This includes increased AVM flow, presence of long pial draining ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
0
28
0
2
Order By: Relevance
“…These pathologic events might be the underlying mechanisms of bAVM-associated declines in sensory and motor functions as well as memory loss (see Fig 6D-L). Patients with bAVMs sometimes develop significant neurological disorders, including epilepsy, dementia, amyotrophic lateral sclerosis, or Parkinson's disease [57][58][59][60][61] ; therefore, further studies utilizing our approach can provide new insights into the pathogenesis of neurological diseases related to vascular malformation or vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…These pathologic events might be the underlying mechanisms of bAVM-associated declines in sensory and motor functions as well as memory loss (see Fig 6D-L). Patients with bAVMs sometimes develop significant neurological disorders, including epilepsy, dementia, amyotrophic lateral sclerosis, or Parkinson's disease [57][58][59][60][61] ; therefore, further studies utilizing our approach can provide new insights into the pathogenesis of neurological diseases related to vascular malformation or vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, Josephson et al ( 110 ) reported that AEDs had limited effect on reducing the seizure risk in patients with ruptured temporal bAVMs. If anticonvulsant therapy failed to control seizures, surgical management might be pursued ( 271 ).…”
Section: Resultsmentioning
confidence: 99%
“…Institutional studies have employed both hydrocephalus and epilepsy for risk stratification in AVM microsurgery. [22][23][24] We analyzed associations between patient frailty status and binary outcomes using multivariate logistic regression and reported odds ratios. To evaluate LOS and hospitalization costs, we used gamma regression with a logistic link function, idealized for modeling right-skewed, continuous outcomes, and reported β-coefficients (percentage change in the outcome relative to a reference category).…”
Section: Discussionmentioning
confidence: 99%